Silver Nanoparticle Arrays onto Glass Substrates Obtained by Solid-State Thermal Dewetting: A Morphological, Structural and Surface Chemical Study - Agustín Badán, Juan; Navarrete-Astorga, Elena; Henríquez, Rodrigo; Martín-Jiménez, Francisco de Paula; Ariosa, Daniel; Ramos-Barrado, José Ramón; Dalchiele, Enrique A. (IOAP-MPDI, 2022)
Silver nanoparticles (NPs) on glass substrates were obtained by a solid-state thermal dewetting (SSD) process using vacuum-evaporated-silver precursor layers. An exhaustive investigation of the morphological, structural, and surface chemistry properties by systematically controlling the precursor film thickness, annealing temperature, and time was conducted. Thin silver films with thicknesses of 40 and 80 nm were deposited and annealed in air by applying a combined heat-up+constant temperature–time program. Temperatures from 300 to 500 °C and times from 0 to 50 min were assayed. SSD promoted the morphological modification of the films, leading to the Ag NPs having a discrete structure. The size, shape, surface density, and inter-nanoparticle distance of the nanoparticles depended on the initial film thickness, annealing temperature, and time, exhibiting a cubic silver structure with a (111) preferred crystallographic orientation. The prepared NPs were found to be highly enriched in the Ag{111}/Ag{110}/Ag{100} equilibrium facets. SSD not only promotes NP formation but also promotes the partial oxidation from Ag to AgO at the surface level. AgO was detected on the surface around the nanoparticles synthesized at 500 °C. Overall, a broad framework has been established that connects process factors to distinguish resultant Ag NP features in order to develop unique silver nanoparticles for specific applications.
Keywords: Plata; Silver; Nanoparticles; Solid state dewetting; Solid state dewetting; Nanostructured layers; Facets